Uboj ali terapija - Marek, Miha (Amfiteater (Ljubljana), 2019)
This article begins by outlining two notions of catharsis: the psychotherapeutic one, from which Grum draws, and the dramatic-theatrical one, as it is understood and realised by Grum in his writing. By looking at the historical development of psychoanalysis, the article first shows that the principle of therapeutic catharsis has little to do with Freudian psychoanalysis and that it even partially negates it. Based on Grum's statements, it continues to give a general definition of the author's understanding of the dramatic and theatrical catharsis. Drawing on three plays by Grum, Weary Curtains, The Rebel, and An Event in the Town of Goga, it further sheds light on the inner workings of a cathartic event which is supposed to unravel the dramatic plot: this event is an actual or symbolic murder performed by the protagonist. The article goes on to argue that this great event invariably fails to bring the desired resolution and is thus relativised already within the dramatic action. At the same time, however, it also points to the elements in these plays that substitute for the relativised cathartic principle. These elements are understood as genuine traces of psychoanalytic principles in Grum's dramatic work. Grum understands dramatic-theatrical catharsis primarily from a medical, perhaps even moral and epistemological point of view, which he applies to an individual (spectator) and, consequently, to society. According to Grum, a theatre play must again become "a purging, a bath one takes to cleanse. A play that lacks this purging, this catharsis is bad, which ensues from its origins in religious rituals ..." ("Človeštvo", ZD 1 426) "Mankind", CW 1 426. "A good play is the one that leaves the spectator as kind-hearted and relaxed as a religious person leaving church after witnessing the communion of the Body of Christ" (ZD 2 435) CW 2 435. However, it is difficult for modern plays to integrate this purging moment, because the transcendent authority bringing it about is gone: "Writing a good play is genuinely difficult nowadays, because there is no deity, because we have lost god as the one who was resolving existential conflicts in the old plays and represented a redeeming principle of sorts, who repaid the good and punished the evil and made everything turn out nicely in the play, leaving the spectator satisfied, redeemed and cleansed. Modern plays conclude with unresolved conflicts that leave the spectator doubting and heart-broken, they do not redeem him" (426). Acknowledging that Grum employed his uniquely understood principle of catharsis as a dramaturgical principle in constructing his dramatic works, we may do well to ask ourselves about the mechanism of catharsis in dramatic works, about how catharsis is realised, about its sources, and especially about the effects of the cathartic event. In all his finished dramatic texts, Grum uses murder as an act aimed precisely at resolving the dramatic plot or the destiny of the protagonist. As argued by Zadravec, Grum's "characters opt for a violent liquidation of the paranoid motif and the person as their 'purging bath', that is, they choose murder. But when they fail to enact this act of liquidation, they either harden or shrivel up, or they go mad" (Elementi 400) Elements 400. The article takes a closer look at three of Grum's texts which include a cathartic murder: Weary Curtains (1924), in which Larsen symbolically kills Amara; The Rebel (1927), in which the painter Madonna kills a random mother with a child, that is, the symbolic mother; and An Event in the Town of Goga (1928), in which Hana symbolically kills Prelih. Grum's An Event in the Town of Goga is considered one of the most original Slovenian dramatic texts and belongs to the canon of modern Slovenian playwriting at the break from early modernism and symbolism to the avant-garde and modernist forms. The play describes the communal life in the town of Goga with all its pathologies and the collective hope for a ground-breaking change. The hope of the town of Goga is oriented toward the expectation of the big Event that will transform the community and propel it into the sphere of "the bright new life". At the end of the play, this hope is disappointed, as even the painter, who has been rooting vigorously for the event, lowers his head in surrender (ZD 1 235) CW 1 235. The great Event does not take place - that is the message of the play. The community of Goga has not changed, not everything has become new. The same can be argued if we look at Hana's story as the central one. As has been shown, Hana did not experience her own redeeming Event. However, instead of one great Event, several smaller events happen in the play, especially to Hana and Klikot. Hana confesses to Tereza, confronts Prelih, who is the personification of her trauma, and tries to recover (but, as is shown, fails to do so). Klikot is forced into a reality check, first with Kvirin's and Kaps' serenade, and later, with Hana's seduction. He does not succumb to the ordeal, but instead emerges more mature. 179Here, we can recall the initial oxymoron, the phrase "psychoanalytic catharsis", and the fact that Freud rejected cathartic therapy as soon as he discovered the complexity of the analytical method. From a psychoanalytic point of view, the perspective of absence or even of the impossibility of the great Event that would heal everything is of no grave concern; on the contrary, it is an integral part of Freudian therapeutic realism. In the Freudian perspective, healing is not a momentary event that would cancel out the core of a pathology in a single stroke, but entails a gradual workingthrough of one's insights into an elaborate network of psychological phenomena and mechanisms. This working-through is never final and its efficacy is not guaranteed. A messianic Event that would change everything, that would bring "a wholly altered, bright new life" happens neither in Goga nor in psychoanalytic therapy. Every event promising to do so is a false hope. In this sense, Vladimir Bartol is right to call An Event in the Town of Goga a "psychoanalytic play".
Keywords: catharsis; entrapment; katarza; murder; psihoanaliza; psychoanalysis; Slavko Grum; terapevtski dogodek; therapeutic event; uboj; ujetost